1994
DOI: 10.1055/s-2007-1021083
|View full text |Cite
|
Sign up to set email alerts
|

Adding Polylactate to a Glucose Polymer Solution Does Not Improve Endurance

Abstract: Polylactate (PL), a semi-soluble amino acid/lactate salt, is a newly developed carbohydrate supplement purported to increase endurance. Our purpose was to determine if the addition of PL to a glucose polymer solution (GP) extends exercise time relative to a pure GP solution. In a double blind and random crossover design, 5 subjects exercised twice to exhaustion at 70% of VO2max. During the trials, they consumed GP or a GP/PL mixture at the rate of 0.3 g carbohydrate per kg of body wt in a 7% solution every 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
1
19
0
3
Order By: Relevance
“…In fact, the oral ingestion of lactate (in the form of polylactate, sodium lactate or calcium lactate) has been studied since 1991, when Fahey and colleagues concluded that lactate may be used as an energy substrate to help maintain blood glucose during endurance exercise. Although one study has shown a remarkable 25% improvement in endurance exercise performance following lactate supplementation (Azevedo et al, 2007), most studies have failed to show any benefit (Bryner et al, 1998;Northgraves et al, 2013;Preveler & Palmer, 2012;Swensen et al, 1994).…”
mentioning
confidence: 97%
“…In fact, the oral ingestion of lactate (in the form of polylactate, sodium lactate or calcium lactate) has been studied since 1991, when Fahey and colleagues concluded that lactate may be used as an energy substrate to help maintain blood glucose during endurance exercise. Although one study has shown a remarkable 25% improvement in endurance exercise performance following lactate supplementation (Azevedo et al, 2007), most studies have failed to show any benefit (Bryner et al, 1998;Northgraves et al, 2013;Preveler & Palmer, 2012;Swensen et al, 1994).…”
mentioning
confidence: 97%
“…A number of researchers have investigated the influence of polylactate ingestion on endurance performance (2,3,19,22), since Brooks (1) found that lactate can serve as an energy source for exercising muscles. In the study of Fahey et al (3), the ingestion of 80% polylactate and 20% sodium lactate as a 7% solution in water increased blood pH and bicarbonate compared to ingestion of a glucose polymer drink.…”
mentioning
confidence: 99%
“…Prior to the present research, two other studies sought to determine the efficacy of lactate as a sports drink component [5], [16]. Neither study utilized tracers to quantify metabolite fractional oxidation rates as was done in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, the efficacy of adding lactate to these drinks has been sparsely assessed [5], [15], [16]. Lactate was once considered a metabolic waste but is now recognized as an important energy substrate in the body.…”
Section: Introductionmentioning
confidence: 99%